Chronic Tenosynovitis of the Upper Extremities Caused by Mycobacterium kansasii: A Clinical Case and Systematic Review of Literature - Maria T. Huayllani; Andrea Sisti; Daniel Boczar; David J. Restrepo; Alexander S. Parker; Rachel Sarabia-Estrada; Brian D. Rinker; Antonio Jorge Forte (Indian Journal of Plastic Surgery)
Background Chronic tenosynovitis of the upper extremities caused by Mycobacterium kansasii (M. kansasii) is uncommon, but symptoms may overlap with other more common diseases. Late diagnosis and treatment can lead to disfiguration of structures and rupture of tendons, resulting in worse cosmetic outcomes after reconstruction. Methods We present a clinical case and literature review of M. kansasii in patients with chronic tenosynovitis of upper extremities. PubMed was queried for cases of upper extremities tenosynovitis caused by M. kansasii. The keywords “M. kansasii,” “tenosynovitis” and synonyms were used for search in different combinations. Manuscripts, with no specific data or another condition, where the infection was not located in the upper extremities, were reviews, or not in English, were excluded from the study. Results We described 23 reported cases of tenosynovitis of the upper extremity caused by M. kansasii. An immunosuppressed state was present in eight (34.8%) cases, and 12 (52.2%) patients received immunosuppressive treatment. A long-time period between the first appearance of symptoms and the definitive diagnosis was identified (median: 7 months, interquartile range: 9). The most frequent symptoms were local swelling (65.2%), pain (56.5%), mass effect (26%), and stiffness (13%). Tendon rupture was found in three (13%) patients as a complication of the disease. Moreover, seven (30.4%) patients underwent previous surgeries to try to relieve the symptoms before definitive diagnosis was achieved. Conclusion M. kansasii is an important differential causal pathogen for tenosynovitis of the upper extremities. Although rare, raising awareness about this infectious disease is imperative to avoid inadequate management and hazardous aesthetic sequelae.